Caracterização da atividade pró-oxidante de diferentes agentes e estudo do potencial antioxidante de intermediários do ciclo de Krebs sobre alterações oxidativas induzidas in vitro - Puntel, Robson Luiz (2008)
Previous data from the literature have shown that some Krebs cycle intermediates could act as antioxidant in several models, both in vitro and in vivo. However, the mechanism(s) involved in the antioxidant effect of Krebs cycle intermediates are not fully understood. Additionally, there are scarce data in the literature taking into account the in vitro effect of Krebs cycle intermediates during oxidative stress conditions. Thus, the aim of this study was to determine the effect of some Krebs cycle intermediates on lipid peroxidation induced in vitro by different pro-oxidant agents, and the mechanism(s) by which they act. Furthermore, it was necessary elucidate the mechanisms by which the different pro-oxidants acts under in vitro conditions. The present results showed that the malonate-induced TBARS production was not changed by potassium cyanide or MK-801. However, the pro-oxidant effect of quinolinic acid was significantly prevented by MK-801. In addition we found that both malonate and oxalate were able to form complexes with iron ions (Fe2+). Based on the presented results, we conclude that malonate pro-oxidant activity in vitro seems to be independent of the secondary excitotoxicity via indirect NMDA receptors activation. Additionally, we suggest that both the malonate and oxalate effect, in these experimental conditions, is due to its ability to form complexes with iron ions, thus modulating an adequate ratio Fe2+/Fe3+ that could cause an increase in free radicals generation. In contrast, the quinolinic acid effect seems to be dependent of the NMDA receptors activation. However, we can not rule out the involvement of iron ions in quinolinic acid toxicity under our assay conditions. Another objective of this study was to investigate the effect of some Krebs cycle intermediates against either basal or induced TBARS production, using rat brain S1 preparations and the mechanism(s) by which they act. The results showed that oxaloacetate, citrate, succinate, and malate were able to significantly prevent both basal and quinolinic acid-, iron- or malonate-induced TBARS production. On the other hand, fumarate prevented only malonate-induced TBARS production, without effect under basal conditions. However, α-ketoglutarate induced per se a significant increase in basal TBARS production. The antioxidant activity of fumarate and succinate were completely abolished when S1 was submitted to heat-treatment at 100ºC during 10 min. Likewise, potassium cyanide completely abolished the antioxidant effect of succinate. The effect of other Krebs cycle intermediates studied was unchanged with respect to heat-treatment, or cyanide. Except for succinate and fumarate, all intermediates used in this study were able to form complexes with iron (Fe2+) ions, however only oxaloacetate and α-ketoglutarate significantly prevented deoxyribose degradation induced by hydrogen peroxide. Based on the results presented, we concluded that oxaloacetate, malate, succinate, fumarate and citrate could act as antioxidants under such conditions, whereas α-ketoglutarate acts as a pro-oxidant agent per se. The mechanism(s) by which citrate, malate, and oxaloacetate acts seems to be related to their ability to form complexes with iron (Fe2+) ions, thus modulating the iron redox cycle. In contrast, the succinate and fumarate antioxidant effect seems to be dependent of the some enzymatic system.